Non-Haredi Arts Therapists’ Perceptions of Therapy With Ultra-Orthodox Children - Keidar, Lali; Regev, Dafna; Snir, Sharon (Frontiers in Psychology, 2021)
Studies have underscored the complexity of the encounter between ultra-Orthodox (Haredi) society and psychotherapy, as well as the challenges involved in developing a therapeutic relationship in cross-cultural therapy. However, there is scant research on therapy for ultra-Orthodox children, especially when it comes to arts therapies that take place in a cross-cultural setting. The current study examined the perceptions of 17 arts therapists (including visual art therapists, dance/movement therapists, psychodramatists, music therapists and bibliotherapists) who are not ultra-Orthodox, and who currently work or have previously worked with ultra-Orthodox children. Semi-structured interviews were conducted with the therapists and analyzed using the principles of Consensual Qualitative Research. The study covered four domains: 1) perceptions of the significance and objectives of arts therapy with ultra-Orthodox children; 2) the influence of the cultural difference between therapist and client on the emotional experience and the therapeutic relationship; 3) the use of arts in therapy; 4) systemic aspects. The findings indicate significant perceptual and value-based disparities between therapists and clients, which pose difficulties and challenges to all participating parties and require therapists to be highly sensitive. Aside from the difficulties, the findings suggest that this cultural difference may also have certain advantages for clients as well as therapists. The findings likewise attest to the multifaceted process of change that is taking place within Haredi society in its attitude towards psychotherapy in general and arts therapy in particular.